Editing Citrus Genome via SaCas9/sgRNA System - Jia, Hongge; Xu, Jin; Orbović, Vladimir; Zhang, Yunzeng; Wang, Nian (Frontiers in Plant Science, 2017)
SaCas9/sgRNA, derived from Staphylococcus aureus, is an alternative system for genome editing to Streptococcus pyogenes SpCas9/sgRNA. The smaller SaCas9 recognizes a different protospacer adjacent motif (PAM) sequence from SpCas9. SaCas9/sgRNA has been employed to edit the genomes of Arabidopsis, tobacco and rice. In this study, we aimed to test its potential in genome editing of citrus. Transient expression of SaCas9/sgRNA in Duncan grapefruit via Xcc-facilitated agroinfiltration showed it can successfully modify CsPDS and Cs2g12470. Subsequently, binary vector GFP-p1380N-SaCas9/35S-sgRNA1:AtU6-sgRNA2 was developed to edit two target sites of Cs7g03360 in transgenic Carrizo citrange. Twelve GFP-positive Carrizo transformants were successfully established, designated as #Cz1 to #Cz12. Based on targeted next generation sequencing results, the mutation rates for the two targets ranged from 15.55% to 39.13 for sgRNA1 and 49.01% to 79.67% for sgRNA2. Therefore, SaCas9/sgRNA can be used as an alternative tool to SpCas9/sgRNA for citrus genome editing.